Witness Simulation Of Flight Arrival And Departure For One Runaway Airport Design - Suhatri, Nur Syakila (Universiti Sains Malaysia, 2021)
Aircraft turnaround processes involved the process from the moment aircraft arrive until it departs again. Some of the processes involved during aircraft turnaround such as refueling, disembarking, cleaning, passengers boarding and others. Therefore, low aircraft turnaround time is desired in order to avoid delay which is the common problem in aviation industry and will directly impacted customer trust. This research was proposed based on Kulim International Airport (KXP) project that is currently in planning stage. The aims is to study the aircraft turnaround process for a Boeing 737-800 by using Witness Horizon simulation software. Four models of aircraft turnaround with different situation were developed and analyzed in this research. The models are no breakdown model, breakdown on catering vehicle model, breakdown on fuel truck model and breakdown on both catering vehicle and fuel truck. The result of each model is analyzed based on parts, machines and labor performance. Each section is then compared based on percentage of busy, percentage of idle, percentage of breakdown, average WIP and others. A table of comparison of all models was created to choose the optimal model. The optimal model is no breakdown model as it has the nearest aircraft turnaround time with the proposed aircraft turnaround time of a Boeing 737-800 of 37 minutes. Any breakdown as modelled in the simulation will directly impacted flight schedule and causes delays.